2008
DOI: 10.1097/shk.0b013e318157e926
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Glycocalyx Damage During Endotoxemia Coincides With Microcirculatory Dysfunction and Vascular Oxidative Stress

Abstract: The glycocalyx constitutes the first line of the blood tissue interface and is thus involved in many physiological processes, deregulation of which may lead to microvascular dysfunction. Because administration of LPS is accompanied by severe microvascular dysfunction, the purpose of the study was to investigate microvascular glycocalyx function during endotoxemia. Bolus infusion of LPS (10 mg kg(-1)) to male Sprague-Dawley rats elicited the development of hyporeactivity to vasoactive agents and microvascular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
122
2
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(136 citation statements)
references
References 30 publications
3
122
2
9
Order By: Relevance
“…There are alterations in the glycocalyx, the thin protein on the surface of the endothelial cell that contains antithrombin and superoxide dismutase. There is also a decrease in is size [25][26][27] and increase in its products of degradation in the blood [26,28]. This in turn leads to leukocyte rolling and adhesion to the surface of the endothelium as well as impairing the circulation of RBCs leading to impaired release of nitrous oxide (NO).…”
Section: Microvascular Alterations and Perfusion Heterogeneitymentioning
confidence: 99%
“…There are alterations in the glycocalyx, the thin protein on the surface of the endothelial cell that contains antithrombin and superoxide dismutase. There is also a decrease in is size [25][26][27] and increase in its products of degradation in the blood [26,28]. This in turn leads to leukocyte rolling and adhesion to the surface of the endothelium as well as impairing the circulation of RBCs leading to impaired release of nitrous oxide (NO).…”
Section: Microvascular Alterations and Perfusion Heterogeneitymentioning
confidence: 99%
“…Interestingly, it seems that the anticoagulant properties of the drug may not be implicated in these microvascular effects. Improvement in white blood cell rolling and adhesion as well as preservation of glycocalyx may also be implicated (20,(52)(53) .…”
Section: Anticoagulantsmentioning
confidence: 99%
“…All animal studies assessing the effects of activated protein C on microcirculation reported a beneficial effect (20,(52)(53) . We showed evidence of a beneficial impact on perfused capillary proportion as early as four hours after the beginning of activated protein C infusion in septic patients with an on/off pattern (54) .…”
Section: Anticoagulantsmentioning
confidence: 99%
See 2 more Smart Citations